Władza książęca na Pomorzu do Warcisława I - Kruszewski, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The author examines the origins of ducal rule in Pomerania, finding them in Świętopełk, the son of Mieszko I. He rejects the nineteenth-century concept of the origins liked a duke allegedly baptised by St. Adalbert. He supports the view of those who acknowledge the non-existence of statehood before Mieszko I’s conquest. Pomerania was a region under imperial rule and any criticism of Edward Rymar’s views testifies to an insufficient knowledge of history and law. A debate over the issue will not be productive. Pomerania is a Conradian “heart of darkness”, but the principles of patrimonial monarchy unequivocally settle the most important questions. For a historian of political systems and law, J.M. Piskorski’s dilemma concerning the number of ducal dynasties in Pomerania is totally incomprehensible. Supreme rulers cannot be mixed with some minor magnates. From Mieszko I to Bogusław XIV and Mszczuj II not forgetting the meanders of the return to power of the latter’s ancestors the region was ruled by one dynasty. Drawing any legal conclusions titles from the information provided by Gallus is a mistake. Creating a history out of some “ipse dux”, for example, in the form of a duke from a competing dynasty, or, worse still, Warcisław I’s alleged father, when Gallus dowa not even mention the name of that “ipse dux”, can lead to the only conclusion that this was a minor figure, which, after all J. Dowiat demonstrated already in 1954. This may even have been Świętobor II’s count palatine, who deposed the ruler, which forced Bolesław III the Wrymouth to intervene. There was just one dynasty.
Keywords: wieki średnie; monarchia patrymonialna; Polska; Pomorze